Validation of the Social Well-being Scale in an Iranian Sample - Mostafa Zahirinia; Hassan Khezri (Iranian Journal of Educational Research)
Objective: Social well-being stands as a pivotal component of individuals' holistic well-being and quality of life, indicating their contentment with social connections, societal contributions, and sense of affiliation. The assessment of social well-being across diverse populations holds paramount importance in elucidating the variations in individuals' experiences and facilitating interventions aimed at bolstering their well-being. Hence, the present study sought to assess the validity and reliability of the Social Well-being Scale devised by Corey Keyes within an Iranian sample. Methods: The study adopted a descriptive-psychometric approach, with the statistical population comprising all females aged 20-50 in Hormozgan province, Iran in the year 2022. A sample size of 300 women was selected through stratified sampling. The study incorporated the employment of the Well-being Scale created by Corey Keyes (1998) and the Psychological Well-Being Questionnaire developed by Ryff et al. (2010). Results: The outcomes of the confirmatory factor analysis demonstrated a satisfactory model fit, aligning with the five-factor model as per the original theoretical framework. Moreover, further validation was established through statistically significant correlations identified between dimensions of social well-being and scores on psychological well-being. The reliability analysis also indicated strong internal consistency across all dimensions of well-being. Conclusions: The adoption of this reliable and validated scale proves to be instrumental in evaluating social well-being during adulthood within the Iranian context. It not only enables a more comprehensive exploration of mental health research but also facilitates opportunities for assessment and intervention grounded in a positive paradigm.